2012
DOI: 10.3113/fai.2012.0014
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Medial Gastrocnemius Release in the Treatment of Recalcitrant Plantar Fasciitis

Abstract: We believe a PMGR is a simple way of treating a patient with PF who has failed to respond to conservative management. In our series, the results were favorable, the recovery fast and the morbidity low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
117
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(130 citation statements)
references
References 22 publications
3
117
0
2
Order By: Relevance
“…In a prospective study, the PMGR has shown excellent results in the treatment of recalcitrant plantar fasciitis [4]. Our results in the PMGR group are almost identical.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…In a prospective study, the PMGR has shown excellent results in the treatment of recalcitrant plantar fasciitis [4]. Our results in the PMGR group are almost identical.…”
Section: Discussionsupporting
confidence: 72%
“…More recently this technique has been modified so that only the medial head of the gastrocnemius is released through a small posterior incision, placed more medially [4]. Additionally, the approach to the medial head was less likely to risk cutaneous nerve damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent anatomic study revealed that the superficial part of the Achilles tendon is mainly from the medial head of the gastrocnemius and has continuity with the plantar fascia [22]. Only releasing the medial head may safely achieve a relatively satisfactory correction of the contracture [10,23,24]. However, patients with a larger equinus contracture of more than 15°of plantar flexion may still suffer from some degree of equinus postoperatively [10].…”
Section: Discussionmentioning
confidence: 96%
“…16 Various surgical procedures have been used for the treatment of resistant plantar fasciitis, but the outcome varies, 14 owing to the diversity of the underlying pathology (such as entrapment of the first branch of lateral plantar nerve, tight Achilles tendon, increased calcaneal intra-osseous pressure and venous congestion, calcaneal periostitis, and presence of calcaneal spur). 5,6,11,14,15,17 Spur excision can be through a medial incision. 18 The optimal site for drilling multiple holes in the calcaneus remains controversial.…”
Section: Resultsmentioning
confidence: 99%